The sugar industry in the contemporary economic history of Passi, Iloilo - Ellano, Joel P.
This study employs the concept multiplier effect, which refers to the widespread effect of an operative catalyst, to an important factor introduced to an economy, and by which concept the economic of the community can be determined. In the instant study, the sugar industry in Passi, especially the two sugar centrals (one is in San Enrique), is the catalyst that is supposed to propel the economic development of the town. By the use of the principle of multiplier effect, it has been determined that the sugar industry, especially the two sugar centrals, has brought about the development of the other sectors of the Passi economy.